PROSPEK PENGEMBANGAN USAHA BUDIDAYA AYAM KETAWA DI KOTA KENDARI - Robin Robin; La Ode Nafiu; Muh. Rusdin (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2015)
The purpose of this research is to study the prospect, problem fared and formulate the developing strategy of raising the chicken laugh at Kendari. The results of this study are expected to be useful as a reference basis for government and practitioners in developing chicken laugh at Kendari and as a reference for further research. The study was conducted in October - November 2012 held at Kendari. Determination of sub-sample study conducted by purposive sampling based on the amount of chicken population Ketawa most, the samples used were each 10 Baruga farmers in the district, sub-district and district Poasia Kadia. Methods of data collection that is through interview, observation and documentation. Data analysis was performed based on a percentage of the value and use SWOT analysis then reviewed descriptively. Prospects for business development in the chicken laugh Kendari supported by the high price of chicken laugh, the majority of farmers belong to the productive age and height HR breeders. The problem faced by the chicken business is a sideline laughing, limited capital breeder, the lack of a stable market and a lack of knowledge and skills in disease control. Based on the results of the SWOT analysis of the development strategy of the management training needs of business in the form of training and directing his efforts into marketoriented core business, utilizing every event as a marketing contest chicken laughing and following exhibitions farms, businesses need to expand the scale poultry laughing, maximizing roles and functions ASPAK for scheduled contests, and disease control training, need guidance from the government in the form of skills training maximal disease controlKeywords: outlook, strategy, development, chicken laugh, City KendariABSTRAKTujuan penelitian ini adalah mengkaji prospek usaha budidaya ayam ketawa di Kota Kendari.. Penelitian dilaksanakan pada bulan Oktober – November 2012 bertempat di Kecamatan Baruga, Kecamatan Kadia dan Kecamatan Poasia Kota Kendari. Penentuan kecamatan sampel penelitian dilakukan secara purposive sampling berdasarkan jumlah populasi ayam Ketawa terbanyak. Jumlah responden di masing-masing Kecamatan lokasi penelitian sebanyak 10 orang peternak, sehingga seluruhnya berjumlah 30 orang responden. Metode pengumpulan data melalui wawancara, observasi dan dokumentasi. Analisis data berdasarkan nilai presentase dan menggunakan analisis SWOT kemudian diulas secara deskriptif. Hasil penelitian menunjukan bahwa prospek pengembangan usaha ayam ketawa di Kota Kendari didukung oleh tingginya harga ayam ketawa, mayoritas peternak tergolong usia produktif dan tingginya SDM peternak. Permasalahan yang dihadapi yakni usaha ayam ketawa bersifat sambilan, modal usaha peternak terbatas, belum adanya pasar yang stabil dan kurangnya pengetahuan dan keterampilan dalam pengendalian penyakit. Berdasarkan analisis SWOT maka strategi pengembangannya yakni perlu pembinaan manajemen usaha dalam bentuk pelatihan dan mengarahkan usahanya menjadi usaha pokok yang berorientasi pasar, meningkatkan skala usaha ternak, memaksimalkan peran dan fungsi ASPAK untuk menyelenggarakan kontes ayam ketawa serta pameran-pameran peternakan, perlu adanya pembinaan pengendalian penyakitKata Kunci : Prospek, strategi, pengembangan, ayam ketawa, Kota Kendari